Synthesis, characterization, photophysical, and photochemical properties of novel zinc(II) and indium(III) phthalocyanines containing 2-phenylphenoxy units - ALTUN, SELÇUK; ODABAŞ, ZAFER (ELSEVIER SCIENCE BV, 2016)
The synthesis of highly soluble and non-aggregated peripherally/non-peripherally Zn and In(OAc) phthalocyanines was achieved by 3-/ and 4-(2-phenylphenoxy)phthalonitrile as starting materials. The novel compounds were characterized by elemental analyses, FT-IR, H-1-NMR (for phthalonitriles), UV-vis and MALDI-TOF mass (for Pcs) spectroscopic techniques. Additionally, photophysical, photochemical and spectral properties of the phthalocyanines were reported. Especially, the indium(OAc) phthalocyanines showed good singlet oxygen quantum yields in DMSO and they can be appropriate candidates as Type II photosensitizers in photodynamic therapy (PDT) applications. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Phthalocyanine; 2-Phenylphenol; Photochemical; Photophysical; Fluorescence; Singlet-oxygen; PHOTODYNAMIC ACTIVITY; SUBSTITUENTS; DERIVATIVES; BEHAVIOR